Incidencia de la orientación de las tareas extra clase de los padres de familia en el rendimiento académico de los estudiantes de 5to año de educación básica de los paralelos A, B, C, de la Escuela Fiscal de Niñas Sulima García Valarezo del cantón Machala , periodo 2012-2013. - Chillogalli Chillogalli, Luis Angel (2012)
The family is the backbone in the formation of the children, which are constructed values, habits, customs each brings to this education before reaching classroom, the child goes with values already formed from the home. That is why the present research work makes a specific study of the influence of the orientation of the class parents in the academic performance of students Sulima girls' school tax Garcia Valarezo extra chores.